Auto-Ignition and Numerical Analysis on High-Pressure Combustion of Premixed Methane-Air mixtures in Highly Preheated and Diluted Environment. Issue 15 (18th November 2022) - Garnayak, Subrat; Elbaz, Ayman M; Kuti, Olawole; Dash, Sukanta Kumar; Roberts, William L; Reddy, V. Mahendra
ABSTRACT: This work investigates both autoignition and combustion characteristics in highly preheated and diluted combustion of a laminar premixed stoichiometric CH4 /O2 /N2 mixture in a cylindrical combustor operating at elevated pressures. The analysis was carried out for a range of operating parameters, including reactant preheat temperatures of 1100–1500 K, combustor pressures of 1-10 atm, and in a highly diluted mixture, achieved by decreasing the oxygen content in the oxidizer from 21% to 3% on volume basis. Simulations were conducted using the laminar premixed adiabatic PFR (plug flow reactor) model of Ansys Chemkin Pro. Two-dimensional pictorial representation was performed using the finite volume-based CFD code Ansys Fluent 19.2. Finite-rate chemistry with the detailed chemical mechanism GRI Mech 3.0 was used for combustion analysis. Results showed that OH and HCO mole fractions decreased with increasing combustor pressure and N2 dilution (or decreased O2 content), while the mole fractions increased with reactant temperature. It was also found that, by reducing the oxygen content in the mixture, the flame stabilized far away from the combustor inlet. In contrast, an increase in combustor pressure and reactant temperature stabilized the flame toward the combustor inlet. These flame stabilization characteristics at different locations of the combustor are explained in terms of ignition delay time, which were calculated using the closed homogenous reactor (CHR) model available in the Ansys Chemkin Pro package. The flame peak temperature decreased with increased N2 dilution and increased by increasing the reactant temperature. Moreover, the peak temperature varied marginally when the combustor pressure was increased. Finally, a regime diagram was prepared to show the various combustion modes, such as HiTAC, MILD combustion, and the no ignition region as a function of O2 content and reactant temperature for different operating pressures. The CO and NO emission were reduced with an increase in pressure in the MILD combustion region.